2017
DOI: 10.1055/s-0043-118180
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation after Stroke

Abstract: Respiratory dysfunction is a common complication following a stroke; however, the pulmonary rehabilitation of stroke patients has not been heavily emphasized until recently. PUBMED databases were searched systematically (since inception to December 2016) using the following search terms: “stroke” in Title/Abstract and “pulmonary rehabilitation” in all field. Articles published in a language other than English excluded. The original search yielded 404 articles, of which 57 articles were included in this systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Moreover, IMT + EMT and IMT also improved MIP and MEP. Early stroke patients may have decreased respiratory muscle strength due to respiratory centre injury and central diaphragm dysfunction [ 12 , 29 , 53 , 54 ], while RMT may improve the integration and regulation of respiratory-related sensory input by promoting the recovery of cerebral cortex respiratory centre [ 9 , 53 ] and activating cortical spinal cord pathway [ 12 , 55 ], thereby improving diaphragm function and respiratory muscle strength. Furthermore, RMT is more likely to change the adaptive structure of respiratory muscle [ 56 ] in patients with early stroke, thereby improving the strength of respiratory muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, IMT + EMT and IMT also improved MIP and MEP. Early stroke patients may have decreased respiratory muscle strength due to respiratory centre injury and central diaphragm dysfunction [ 12 , 29 , 53 , 54 ], while RMT may improve the integration and regulation of respiratory-related sensory input by promoting the recovery of cerebral cortex respiratory centre [ 9 , 53 ] and activating cortical spinal cord pathway [ 12 , 55 ], thereby improving diaphragm function and respiratory muscle strength. Furthermore, RMT is more likely to change the adaptive structure of respiratory muscle [ 56 ] in patients with early stroke, thereby improving the strength of respiratory muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, people usually give priority to the recovery of limb dysfunction in patients with early stroke and pay less attention to respiratory dysfunction after early stroke [ 8 ]. Although there is no precise report on the incidence of respiratory dysfunction in early stroke patients, previous studies have found that 18–88% of stroke patients have respiratory dysfunction [ 6 , 9 ]. Research shows that stroke recovery usually occurs within three months of stroke onset, while 15–30% of stroke patients may have permanent dysfunction after 3 months of onset [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [5] entzündlichen oder degenerativen rheumatischen Erkrankungen und Fibromyalgiesyndrom erhoben. Die meisten Patienten erwiesen sich als leicht bis deutlich belastet, ohne klinisch relevante Beeinträchtigungen zu haben, wobei diese Beschwerden über die Zeit recht stabil blieben.…”
Section: Zu Den Themen Des Schwerpunktheftesunclassified